DIFFERENTIAL-SEMANTIC RELATIONS IN LEXICAL UNITS (Scientific journal of the Fergana State University, 2024)
The article discusses issues of studying communicative semantics, speech processes, methods of oppositional, component and text analysis, the structure of lexical-semantic paradigms, as well as issues related to the semantic relations of words.